Composition of Key Board of Director Sub-Committees: Did the Higgs Report Get It Right? - Van der Zahn, Jean-Luc Wolfgang Mitchell (Institutional Knowledge at Singapore Management University, 2005)
The Higgs Report (2003) recommends firms should not allow a director to sit simultaneously on the audit, remuneration and nomination committees. Our study analyzes the Higgs Report (2003) recommendation in regard to the magnitude of earnings. Using 2003 data hand collected from 354 Singapore publicly listed firms our statistical analyze provides three key findings. First, we find firms with audit, remuneration and nomination committees comprising the same individuals were less effective at constraining earnings management than firms having individual membership variation in key subcommittee composition. Second, we report a positive association between the magnitude of earnings management and proportion of individuals sitting on all three key subcommittees of a firm. Finally, contrary to expectations we show firms with no single individual sitting on the audit, remuneration and nomination committees simultaneously were significantly better at constraining earnings management than entities having at least one individual sitting on all three key subcommittees.